2013
DOI: 10.21829/abm104.2013.56
|View full text |Cite
|
Sign up to set email alerts
|

Micromorfología foliar del género Quercus (Fagaceae) en México

Abstract: Mexico is the main center of diversity of the genus Quercus in the Western Hemisphere. Despite recent advances in the knowledge of Mexican oaks, a degree of taxonomic confusion still remains, mainly within particular species complexes. In this study, scanning electron microscopy was used to describe micromorphological foliar structures (trichomes, epicuticular waxes and stomata) from the abaxial and adaxial leaf surfaces of Mexican oak species, with the main goal of assessing the taxonomical utility of these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…(a) (b) The low gs,max in water-saving plant species does not only lie with a reduced stomatal density. The development of an external structure that reduces the stomatal pore area by the deposition of epicuticular waxes, in the form of a protruding overarch, has been described in different Quercus species living in dry habitats [133,134]. A deep functional study about the possible role of this drastic reduction of effective stomatal pore area in Q. coccifera was performed by Roth-Nebelsick et al [135], who evidenced its influence in the reduced value of gs,max showed by this species.…”
Section: Water Saver Strategy Regulates Water Loss At the Expense Of mentioning
confidence: 98%
“…(a) (b) The low gs,max in water-saving plant species does not only lie with a reduced stomatal density. The development of an external structure that reduces the stomatal pore area by the deposition of epicuticular waxes, in the form of a protruding overarch, has been described in different Quercus species living in dry habitats [133,134]. A deep functional study about the possible role of this drastic reduction of effective stomatal pore area in Q. coccifera was performed by Roth-Nebelsick et al [135], who evidenced its influence in the reduced value of gs,max showed by this species.…”
Section: Water Saver Strategy Regulates Water Loss At the Expense Of mentioning
confidence: 98%
“…5 ). In this sense, it is still necessary to quantitatively evaluate the density of trichomes in the leaf lamina, as well as the epidermis type to find out if there are differences among the different taxa (Fortini et al 2015 ; López-Caamal et al 2017 ; Scareli-Santos et al 2013 ; Tschan and Denk 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…y Gual, 2014), usos (Luna-José et al, 2003), exploración de caracteres de importancia taxonómica en el género (Valencia y Barajas-Morales, 1995;Valencia y Delgado, 2003;Vázquez, 2006;Pérez-Olvera y Dávalos-Sotelo, 2008;Scareli-Santos et al, 2013), taxonomía de algunos complejos de especies (Valencia, 2005;Romero, 2006; Vázquez y Nixon 2013) y de diversidad en algunas entidades (Banda, 1974;González-Villarreal, 1986;Bello y Labat, 1987;De la Cerda, 1989;Valencia, 1989Valencia, y 1995Vázquez, 1992;Encina y Villareal, 2002;Romero et al, 2002;Villarreal et al, 2008;Sabás, 2011;Valencia y Nixon, 2011). No obstante el interés y la gran cantidad de información acumulada para este taxon, aún faltan por realizar estudios básicos para conocer con precisión la riqueza específica regional y estatal del género Quercus en México.…”
Section: Introductionunclassified